2014
DOI: 10.1093/hmg/ddt672
|View full text |Cite
|
Sign up to set email alerts
|

Polycystin-1 regulates actin cytoskeleton organization and directional cell migration through a novel PC1-Pacsin 2-N-Wasp complex

Abstract: How epithelial cells form a tubule with defined length and lumen diameter remains a fundamental question in cell and developmental biology. Loss of control of tubule lumen size in multiple organs including the kidney, liver and pancreas features polycystic kidney disease (PKD). To gain insights into autosomal dominant polycystic kidney disease, we performed yeast two-hybrid screens using the C-terminus of polycystin-1 (PC1) as bait. Here, we report that PC1 interacts with Pacsin 2, a cytoplasmic phosphoprotein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
44
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 46 publications
1
44
0
Order By: Relevance
“…Similar changes were also observed in keratinocytes from patients with SM associated with pachyonychia congenita type 2 (1). Polycystin-1 (PC1) is a large (~4,302 residues) integral membrane with 11 transmembrane domains (7). The PC1-Pacsin 2-N-Wasp complex is thought to contribute to the formation and maintenance of normal kidney tubular structures (7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar changes were also observed in keratinocytes from patients with SM associated with pachyonychia congenita type 2 (1). Polycystin-1 (PC1) is a large (~4,302 residues) integral membrane with 11 transmembrane domains (7). The PC1-Pacsin 2-N-Wasp complex is thought to contribute to the formation and maintenance of normal kidney tubular structures (7).…”
Section: Discussionmentioning
confidence: 99%
“…Polycystin-1 (PC1) is a large (~4,302 residues) integral membrane with 11 transmembrane domains (7). The PC1-Pacsin 2-N-Wasp complex is thought to contribute to the formation and maintenance of normal kidney tubular structures (7). The putative role of PC1 in epidermis is unknown (8).…”
Section: Discussionmentioning
confidence: 99%
“…59 We recently found that PC1 is present in the lamellipodia in migrating kidney tubular epithelial cells. 67 binds to an F-bar protein Pacsin 2 and regulates Pacsin 2 interaction with NWasp, an activator of the actin nucleator Arp2/3 protein complex. We found that disorganization of the actin cytoskeleton is a feature of PKD in vivo and that a novel PC1-Pacsin 2-N-Wasp complex is required for the actin remodeling and directional cell migration.…”
Section: Jing Zhoumentioning
confidence: 99%
“…We found that disorganization of the actin cytoskeleton is a feature of PKD in vivo and that a novel PC1-Pacsin 2-N-Wasp complex is required for the actin remodeling and directional cell migration. 67 Directional cell migration is essential for the regeneration and maintenance of the epithelium and kidney development. 68 We propose that a defective actin cytoskeleton and directional cell migration contributes cyst formation.…”
Section: Jing Zhoumentioning
confidence: 99%
“…Although its function in TBI is still unclear, a study has revealed the involvement of PACSIN in signal transduction to the cytoskeleton of neurons through phosphorylation by protein kinase C and casein kinase 2 (8082). Importantly, this phosphorylation of casein kinase 2 has been proven to precipitate Rac1-dependent spine formation in dendrites of hippocampal neurons (83).…”
Section: Discussionmentioning
confidence: 99%